The Concept Of Taradin In Online Buying The study of surah an-Nisa' Version 29 - Nuri Aslami; Nurul Izzah; Azhari Akmal Tarigan (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2021)
Abstrak The Qur'an, as a direction and guide for humans, requires Muslims to understand the verses of the Qur'an. The Qur'an has set rules for humans in seeking sustenance, one of which is by way of muamalah or trading (buying and selling). Trading should not be done with the will of vanity. Allah forbids humans to eat other people's property and harming others in a vanity way. Trading or buying and selling are required to be based on an-taradin' or the willingness between the two parties. This study aims to analyse the concept of 'an-taradin in online buying and selling, which refers to the interpretation of Al-Munir by Wahbah az-Zuhaili. This is a qualitative study. The data were analysed using a literature study. According to Shari'a rules, the results showed that 'An-taradin or mutual consent in Surah An-Nisa' verse 29 is the willingness between the two parties. Mutual willingness must be following the limits of sharia. Online buying and selling transactions are required to have open ethics and trust in the transaction to avoid the detrimental of both parties. Honesty and benefit can be the basic principles in conducting online buying and selling transactions.